Utilization Of Computer-Based Accounting Systems Through The Siapik Application In Micro, Small and Medium Enterprises (Study Case : Shop Mother Mitha in the Regency Maros) - Nurzalsabilah; Azis, Muhammad; Idris, Hariany (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
This research aims to identify and understand the role and impact of a computer-based accounting system through the SIAPIK application on Bunda Mitha Stores, more specifically to explain how this technology can help Mother Mitha Stores in preparing financial reports. The variable in this research is a single variable, namely focusing on the SIAPIK application. The subject of this research is the owner of the Bunda Mitha Shop, while the focus of this research is the bookkeeping of the Bunda Mitha Shop. The data sources used are primary data and secondary data whose collection was obtained through interviews and documentation. Data analysis is carried out by collecting data, inputting data, presenting data and drawing conclusions. The result of using the SIAPIK application is that it has a positive impact on the shop mother Mitha because it can measure the financial performance of its business whether it is profit or loss and produce financial reports such as financial position reports, profit and loss reports and cash flow reports. The SIAPIK application also helps you Mitha Store to check inventory so that there are no excesses or shortages of goods because the inventory is already systemized in the SIAPIK Application.